Property rights, collective action and plant genetic resources - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
Conservation of genetic resources contributes to plant genetic diversity, which includes both the combination of species in agricultural ecosystems, as well as the number of different varieties within a species (genetic diversity). Loss of biodiversity in cultivated and wild species can increase plant vulnerability to insect pests and diseases, worsen nutrition through declines in the variety of foods available, reduce the capacity of plant resources to adapt to changing conditions, and lead to loss of local knowledge about diversity. These effects can in turn reduce food security, threaten the sustainability of agricultural production systems, and jeopardize the livelihoods of rural communities today and for generations to come.